A cosmo-politics of the territory? Dialogues between western genealogy and latinamerican geographies. - Palladino, Lucas (Universidad Nacional del Litoral, 2021)
A bibliographic tour is carried out that focuses on an analysis of the uses and appropriations of the concept of territory, problematizing two issues. On the one hand, the euro-western genesis and the formation of the concept as an analytical category. On the other hand, epistemic emergencies from the ethno-territorial movements in Latinoamerica and contributions as a category of practice. The work is structured in three parts. In the first place, the meanings constructed from Western (Euro) genealogy are briefly addressed; second, the epistemological reaches of the integrative perspective in geography; third, the emergence of interdisciplinary  and practices perspectives, especially  of political ontologies and cosmopolitical.